Q2DW‐Tide and ‐Ionosphere Interactions as Observed From ICON and Ground‐Based Radars. Issue 11 (11th November 2021) - Forbes, Jeffrey M.; Heelis, Roderick; Zhang, Xiaoli; Englert, Christoph R.; Harding, Brian J.; He, Maosheng; Chau, Jorge L.; Stoneback, Russell; Harlander, John M.; Marr, Kenneth D.; Makela, Jonathan J.; Immel, Thomas J.
Abstract: A quasi‐2‐day wave (Q2DW) event during January‐February, 2020, is investigated in terms of its propagation from 96 to 250 km as a function of latitude (10°S to 30°N), its nonlinear interactions with migrating tides to produce 16 and 9.6‐h secondary waves (SWs), and the plasma drift and density perturbations that it produces in the topside F‐region (590–607 km) between magnetic latitudes 18°S and 18°N. This is accomplished through analysis of coincident Ionospheric Connections Explorer (ICON) measurements of neutral winds, plasma drifts and ion densities, and wind measurements from four low‐latitude (±15°) specular meteor radars (SMRs). The Q2DW westward‐propagating components that existed during this period consist of zonal wavenumbers s = 2 and s = 3, that is, Q2DW+2 and Q2DW+3 (e.g., He, Chau et al., 2021, https://doi.org/10.1029/93jd00380 ). SWs in the ICON measurements are inferred from Q2DW+2 and Q2DW+3 characteristics derived from traditional longitude‐UT fits that potentially contain aliasing contributions from SWs (" apparent " Q2DWs), from fits to space‐based zonal wavenumbers that each reflect the aggregate signature of either Q2DW+2 or Q2DW+3 and its SWs combined (" effective " Q2DWs), and based on information contained in published numerical simulations. The total Q2DW ionospheric responses consists of F‐region field‐aligned and meridional drifts of order ±25 ms −1 and ±5–7 ms −1, respectively, and total ion density perturbations of order (±10%–25%). It is shown that the SWs can sometimes make substantial contributions to the Q2DW winds, drifts, and plasma densities. Key Points: The first contemporaneous measurements of Q2DW winds and the topside ionospheric response are reported based on ICON data Q2DW topside F‐region field‐aligned and meridional drifts of ∼25 m/s and ∼6 m/s, and electron density perturbations of ∼10%–25% occurred ICON winds, drifts, Ne, and ground‐based radar‐measured winds contain signatures of Q2DW‐tide nonlinear interactions